Case Report: Toxic encephalopathy caused by repeated inhalation of liquid sealant - Wen, Zixin; Dai, Ping; Zhou, Zhiqiang; Guo, Lanlan; Zhang, Tongyue; Genjiafu, Aerbusili; Jian, Tianzi; Li, Yaqian; Kan, Baotian; Jian, Xiangdong (Frontiers in Public Health, 2022)
Short-term exposure to high levels of organic solvents, as well as long-term exposure to small doses, can damage the central nervous system, thereby leading to toxic encephalopathy. However, toxic encephalopathy caused by long-term inhalation of liquid sealant is rarely reported. This study describes the clinical data of a case of toxic encephalopathy caused by repeated inhalation of liquid sealants and discusses the pathophysiological characteristics and treatment of organic solvent toxic encephalopathy. This report aims to strengthen the understanding of this disease among clinical staff.